2011
DOI: 10.1080/02508060.2011.586552
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosolidarity and beyond: can ethics and equity find a place in today's water resource management?

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…The contributions to the seminar were published in Water International in June 2000 with hydrosolidarity as the leading theme of the issue. It is worth adding that the interest in hydrosolidarity has continued, as reflected by a recent article in that journal by Gerlak and her colleagues (Gerlak et al 2011).…”
Section: Conceptual Development Around Water and Ecosystemsmentioning
confidence: 94%
“…The contributions to the seminar were published in Water International in June 2000 with hydrosolidarity as the leading theme of the issue. It is worth adding that the interest in hydrosolidarity has continued, as reflected by a recent article in that journal by Gerlak and her colleagues (Gerlak et al 2011).…”
Section: Conceptual Development Around Water and Ecosystemsmentioning
confidence: 94%
“…As opposed to “ hidase ” or nationalism that can be seen as a top‐down national‐scale ideology, the notion of hydrosolidarity has been launched as a way to guarantee water access from an equitable standpoint (Lundqvist 1999; Gerlak et al 2009; 2011). Hydrosolidarity builds on human ethics and person to person empathy which is a bottom‐up approach and implies that water use will not jeopardize the use of water by downstream riparians (Falkenmark 2005; Falkenmark et al 2009).…”
Section: Nationalism Vs Hydrosolidaritymentioning
confidence: 99%
“…Co-evolution is characterized by emergent properties in social and hydrologic systems, the focus of which in this paper are emergent water norms (cf. Falkenmark and Folke, 2010;Gerlak et al, 2011). Sivapalan et al (2012) identified three main lines of sociohydrologic research: (1) historical; (2) comparative; and (3) process-focused.…”
Section: Problem Statementmentioning
confidence: 99%